Modeling strategies for enantiomers separation by SMB chromatography - Pais, Luís S. (2009)
Modeling strategies for simulated moving bed adsorbers were studied to compare the simulated moving bed model (SMB) that considers the real shift of the injection and collection points to the true moving bed approach (TMB) that considers liquid and solid flow in opposite directions. The prediction of these two models is compared in terms of steady-state performance, steady-state internal concentration profiles, and transient behavior of the extract and raffinate purities. The influence of the degree of subdivision of the bed in the SMB model predictions is also analyzed and compared with the TMB performance. Model results are compared with experimental results obtained for the chromatographic separation of binaphthol enantiomers.